Mitigating environmental characteristics with integrated design and automated construction approaches for AQH development - Ibrahim, Rahinah (Faculty of Design & Architecture, Universiti Putra Malaysia, 2007)
Industrialised Building Systems (IBS) implementation requires a systemic operational approach from conceptual design to implementation. In doing so, ensuring the movement of knowledge amongst the team members for a timely and within the budget implementation is a major concern because it impacts the long-term sustainability of the completed project. This study attempts to relate recent international findings to the Malaysian context, which recommended the need to look at the life span of property projects and proposing the development of tools and methodologies that could mitigate the knowledge-loss phenomenon. It found some similarities between housing development projects in USA with those of the local public projects. At the conclusion of this paper, it supports the recommendation for a systemic review of the local IBS delivery process by integrating 3D-CAD modelling during the housing development design process. The systemic IBS process is expected to promote a seamless transition towards 4D technology in the building phase.